Over-Expression of Leptin Receptors in Hypothalamic POMC Neurons Increases Susceptibility to Diet-Induced Obesity - Gamber, Kevin M.; Huo, Lihong; Ha, Sangdeuk; Hairston, Joyce E.; Greeley, Sarah; Bjørbæk, Christian (PLOS ONE, 2012)
Diet-induced obesity (DIO) in rodents is characterized by impaired activation of signal-transducer and activator of transcription 3 (STAT3) by leptin receptors (LepRb) within the hypothalamic arcuate nucleus. This signaling defect likely plays an important role in development of DIO. However, the neuro-chemical identity of the leptin-STAT3 resistant arcuate neurons has not been determined and the underlying mechanisms responsible for development of cellular leptin resistance remain unclear. To investigate this, we first measured arcuate gene expression of known key signaling components of the LepRb signaling pathway and tested whether specifically the critical arcuate pro-opiomelanocortin (POMC) neurons are resistant to LepRb-STAT3 signaling in mice given a high-fat-diet (HFD) compared to mice provided a low-fat control diet (LFD). We found that leptin-dependent STAT3 phosphorylation was decreased within POMC neurons of HFD mice. In addition, Leprb mRNA and suppressor of cytokine signaling 3 (Socs3) mRNA were elevated in the arcuate of HFD mice. To investigate whether increased LepRb expression per se in POMC neurons can influence development of DIO and Socs3 expression, we created mice that over-express LepRb selectively in POMC neurons (POMC-LepRb). No differences in body weight, fat mass or food intake were found between LFD POMC-LepRb mice and LFD controls. Surprisingly, body weight, fat mass and caloric intake of HFD POMC-LepRb mice was markedly higher than HFD control mice. In addition, arcuate Socs3 mRNA was increased in HFD POMC-LepRb mice compared to HFD controls. These data show that specifically POMC neurons of DIO mice are resistant to STAT3 activation by leptin, indicating that those cells might play a role in development of DIO. Furthermore, over-expression of LepRb selectively in POMC neurons increases susceptibility to the development of DIO. We propose a model where over-reactivity of the leptin-LepRb signaling system in arcuate neurons may play causal a role in development of diet-induced obesity.